HAZARD IDENTIFICATION OF WELDING IN CONFINED SPACE OF THE CEMENT PRODUCTION COMPANY - Vievi Ruldi Mufaidah; Endang Dwiyanti (The Indonesian Journal of Public Health, 2022)
Introduction: Maintenance of a electrostatic precipitator cooler machine involving welding activities in confined spaces, so the company of cement production need to understand the existing hazard by conducting hazard identification. Welding are related with physical, chemical, mechanical, and electrical hazards that can cause accidents and occupational illnesses. When the welding is carried out in confined spaces, it can increasing the hazards  include chemical hazards in the air, configuration of the building structure, poor airflow, or any combination of existing hazards. Methods: This research aimed to conduct hazard identification on welding activities in confined spaces. The research design used a descriptive observational with cross sectional approach. The research population was the workers who repair the electrostatic precipitator cooler machines. Sample of this research were selected using the Purposive sampling method, 2 welders in the rapping bar and 1 safetyman. Primary data was collected by conducting observation and interviews using checklist sheet, secondary data was obtained by collecting company profile and daily safety reports. Result: The results of the analysis showed that the identified hazards of welding activities in confined space are 5 of mechanical hazards, 4 of atmospheric hazards, 5 of ergonomics hazards, 5 of falling hazards, 6 of physical hazards, 5 chemical hazards, and 4 electrical hazards. Conclusion: The conclusion of this research was the dominant potential hazard come from physical hazards consisting of inadequate light, welding sparks, optical radiation, noise, high pressure gas and hoses. Some hazards inflict accidents and illness due to work on welding in confined space are welding sparks, fume, oxygen and asitelyn gases, as well as toxic and carcinogenic substance i.e. cement and coal dust. Keywords: confined space, hazard identification, welding